The music files - Vicente, Norma Parrot Guerra (Seven Editora, 2023)
Opening a box closed for twenty years, full of clippings from newspapers and magazines on subjects related to the musical environment, such as reviews of concerts and music festivals in Brazil and abroad, articles on music education in Brazil and other countries, translations of articles on music from specialized French Newspapers, the emergence of new composers on the world stage, cut and saved between 1954 and 1997. This was the great motivation for writing this article. From the totalset of these clippings (547), those from the period from 1964 to 1968 (232) were selected and organized chronologically, using three organization criteria: by jornal, by year, and by author. Parto f the methodology used was the checking and comparision of clippings with the original publications contained in the Hemeroteca Digital Brasileira of the Biblioteca Nacional (Brazil), in the collections of Correio da Manhã and Jornal do Commércio. At the end of this process, the article offers numerical surveys in data collection, comparative tables, and concrete results. DOI:https://doi.org/10.56238/alookdevelopv1-049